Carbon Nano‐Onions Made Directly from CO2 by Molten Electrolysis for Greenhouse Gas Mitigation. (19th July 2019) - Liu, Xinye; Ren, Jiawen; Licht, Gad; Wang, Xirui; Licht, Stuart
Abstract: A high yield, low energy synthesis of carbon nano‐onions (CNOs) by electrolysis of CO2 in molten carbonate is presented. Carbon nano‐onions are a recently recognized, less studied morphology of carbon nanomaterials consisting of nested concentric carbon spheroids. Previously, a high yield growth of carbon nanotubes by CO2 electrolysis in molten carbonate was achieved through transition metal nucleation points on the electrolysis cathode. Here, effective low energy CNO synthesis from CO2 is achieved instead by excluding those nucleating agents from the molten carbonate growth medium resulting in a profusion of uniform CNOs, with an increasing diameter correlated to increasing growth time. CO2 transformation to valuable materials, such as CNOs, adds value to CO2 to incentivize consumption of this greenhouse pollutant. For example, CNOs are currently valued 20 000 times higher than coal. Abstract : The first high yield electrosynthesis of carbon nano‐onions (CNOs) by low cost molten carbonate electrolysis is shown. The only reactant, CO2, becomes a useful, valuable resource rather than a greenhouse pollutant as a response to mitigate anthropogenic CO2 . The synthesis is achieved by excluding nucleating agents from the molten carbonate growth medium resulting in a profusion of uniform CNOs.